Influence of porosity on the analysis of sandwich plates FGM using of high order shear-deformation theory. (Fracture and Structural Integrity, 2019)
In this article, the analytical solutions for static of bending analysis of functionally graded sandwich plates using four-variable high order shear-deformation theory is presented. During manufacture of these plates, defects such as porosities can appear. The objective of this paper is to develop a model to employ the new function for analysis the static of functionally graded sandwich plates. However, the material properties of the sandwich plate varies according to a power law P-FGM form through the thickness coordinate depending on the volume fraction of the constituent material. Equilibrium and stability equations are derived based on the present theory. The solution of the problem is derived by using Navier’s technique. The influences of many sandwich plate parameters such of the variation and influences of porosity coefficient, aspect ratio, side-to-thickness ratio and exponent volume fraction will be investigated.
Keywords: Sandwich plates; Bending; FGM; Porosity; High order theory